2013
DOI: 10.3384/ijal.1652-8670.12196
|View full text |Cite
|
Sign up to set email alerts
|

Political participation of older adults in Scandinavia - the civic voluntarism model revisited? A multi-level analysis of three types of political participation

Abstract: This article examines political participation among older adults in österbotten, Finland, and Västerbotten, Sweden. Two specific hypotheses are tested. First, we anticipate that older adults are loyal voters but less avid in engaging in politics between elections. Second, we expect individuallevel resources to explain why older people participate in politics. The article offers two contributions to the literature on political participation of older adults. First, it corroborates earlier findings by showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…In an attempt to provide greater clarity, two main spheres have been identified (e.g., Adler & Goggin, 2005): social and political participation. With regard to older people's civic participation, although there is a large amount of research on their social participation, particularly volunteering (Wilson, 2012), much less is known about their political participation (Nygard & Jakobsson, 2013). With regard to older people's civic participation, although there is a large amount of research on their social participation, particularly volunteering (Wilson, 2012), much less is known about their political participation (Nygard & Jakobsson, 2013).…”
Section: Aging and Political Participationmentioning
confidence: 99%
“…In an attempt to provide greater clarity, two main spheres have been identified (e.g., Adler & Goggin, 2005): social and political participation. With regard to older people's civic participation, although there is a large amount of research on their social participation, particularly volunteering (Wilson, 2012), much less is known about their political participation (Nygard & Jakobsson, 2013). With regard to older people's civic participation, although there is a large amount of research on their social participation, particularly volunteering (Wilson, 2012), much less is known about their political participation (Nygard & Jakobsson, 2013).…”
Section: Aging and Political Participationmentioning
confidence: 99%
“…By and large, previous research on the association between social capital and political participation tends to apply also to older adults. As an example, in a study of older citizens in Europe Goerres (2009Goerres ( , 2007 found the extent of social networks to be positively correlated with voting (2009,2007), and in a study of older Finns and Swedes Nygård and Jakobsson (2013) found membership in voluntary associations to be positively associated with most types of political participation, while interpersonal trust was only positively associated with political protesting.…”
Section: Social Capital and Political Participation: Definitions And mentioning
confidence: 99%
“…Raziskave o politični participaciji starejših kažejo na pozitivno povezavo med izobrazbo in političnim delovanjem (Nygard in Jakobsson, 2013;Melo in Stockemer, 2014). Politična participacija je povezana z višjim socialno-ekonomskim položajem starejših, predvsem pa so bolj politič-no angažirani hkrati tudi bolj izobraženi, saj si med izobraževanjem pridobijo spretnosti za razumevanje kompleksnih političnih in ekonomskih vprašanj.…”
Section: Aktivno Državljanstvounclassified